Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Wang, Xue-Tong; Fu, Rui; Zhou, Ying; Wang, Cheng-Lin; Ren, Guo-Fa; Wang, Xiao-Li; Li, Hui (Environmental science and pollution research international, 2021)
Polycyclic aromatic hydrocarbons (PAHs), as a class of important environmental pollutants, have received considerable concern due to their widespread existence and biological toxicity. The main purpose of this study was to determine concentrations, spatial distribution, possible sources, and potential health risk of PAHs in urban road dust in Shanghai, China. The concentration of Σ 26 PAHs ranged from 53.0 to 28,700 ng g −1 in road dust samples from Shanghai, which is at the low to medium level compared with other areas around the world. PAHs with 4–5 rings were predominant components in road dust. The level of PAHs in road dust was significantly higher than those in soil and river sediment in Shanghai. Six possible sources of PAHs were apportioned by PMF model. The contribution of pyrogenic PAHs accounted for 91.3% of the total PAHs in road dusts. The motor vehicular emission, natural gas, and coal combustion were main sources for urban road dust PAHs from Shanghai. Four dibenzopyrene (DBP) isomers were contributed averagely 75% of total TEQ BaP concentration. DBalP, BaP, DBaiP, BbF, and DBA were main contributors to total carcinogenic potency, which totally contributed from 69.6 to 91.8% (median 89.1%) to total TEQ BaP in urban road dusts of Shanghai. The results of incremental lifetime carcinogenic risk (ILCR) assessment showed that the total risk values exposed to 24 PAHs in road dust were lower than 10 −4 at all sampling sites, indicating that exposure to dust-bound PAHs at present level was unlikely to result in high carcinogenic risk for both children and adults in Shanghai.